Cognitive Neuroscience Meets the Community of Knowledge - Sloman, Steven A.; Patterson, Richard; Barbey, Aron K. (Frontiers in Systems Neuroscience, 2021)
Cognitive neuroscience seeks to discover the biological foundations of the human mind. One goal is to explain how mental operations are generated by the information processing architecture of the human brain. Our aim is to assess whether this is a well-defined objective. Our contention will be that it is not because the information processing of any given individual is not contained entirely within that individual’s brain. Rather, it typically includes components situated in the heads of others, in addition to being distributed across parts of the individual’s body and physical environment. Our focus here will be on cognition distributed across individuals, or on what we call the “community of knowledge,” the challenge that poses for reduction of cognition to neurobiology and to the contribution of cognitive neuroscience to the study of communal processes.